The Study of Taxonomic Affinity in 7 Species of Asteraceae Family Based on Morphological Characters - Elfa Dina Rahmah Nahdloh; Lutfi Adi Hermawan; Hafidha Asni Akmalia; Putri Rabiatul Adawiyah (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2022)
Morphological characters are important characters in determining plant relationships. This study aims to analyze the phenetic relationship of the 7 member of Asteraceae family based on morphological characters. The study was conducted in May – July 2022. We used 7 species of Asteraceae including Ageratum conyzoides L., Ageratum houstonianum Mill, Tithonia diversifolia (Hemsl.) A.Gray., Sonchus arvensis L., Erechtites valerianifolia (Link ex Spreng.) DC., Eupatorium odoratum L., and Tagetes erecta L. The equipment used were cameras, plant description books, and NTSYS software for taxonomic affinity analysis were used in this study. The results of the Asteraceae dendogram analysis showed that 2 clusters were formed, the first cluster containing the species Ageratum conyzoides L., Ageratum houstonianum Mill, Tagetes erecta L., Sonchus arvensis L., and Erechtites valerianifolia (Link ex Spreng.) DC., while the second cluster consisted of Tithonia diversifolia (Hemsl.) and Eupatorium odoratum L. The closest similarity coefficient of 0.8 was in the genus Ageratus in the first cluster and Tithonia diversifolia (Hemsl.) and Eupatorium odoratum L., in the second cluster. Based on this, it can be concluded that the morphological characters that influence the clustering of 7 species Asteraceae in this study are flower type, flower color, leaf base, leaf venation, leaf margin, and leaf color.